1988
DOI: 10.2337/diab.37.5.532
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms in Basement Membrane Complications of Diabetes: Alterations in Heparin, Laminin, and Type IV Collagen Association

Abstract: We report alterations in the ligand-binding properties of laminin, the major noncollagenous protein of basement membranes, resulting from nonenzymatic glycosylation in vitro. Mouse laminin was incubated in vitro with 500 mM glucose, and the level of nonenzymatically glycosylated amino acids increased 2-, 6.2-, and 12-fold after incubation for 1, 3, and 12 days, respectively. Ligand binding assays conducted in solution with varying concentrations of [3H]heparin and a constant amount of control or nonenzymatical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 0 publications
1
13
0
2
Order By: Relevance
“…Studies have shown that prevalence of microalbuminuria is near 10 % in pre-diabetes and 25 % in diabetes [26]. Chronic exposure to abnormal glycemic levels cause oxidative stress, glycation of membrane proteins, and hyperfiltration resulting in microalbuminuria [27,28]. However, it is not very sensitive and specific marker of nephropathy.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown that prevalence of microalbuminuria is near 10 % in pre-diabetes and 25 % in diabetes [26]. Chronic exposure to abnormal glycemic levels cause oxidative stress, glycation of membrane proteins, and hyperfiltration resulting in microalbuminuria [27,28]. However, it is not very sensitive and specific marker of nephropathy.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, perhaps the most likely single explanation for the increased permeability of glomerular basement membranes to plasma proteins in early NIDDM and its relationship with hyperglycemia is some biochemical mechanism. Increased glycation of laminin and type IV collagen components of the glomerular matrix cause decreased incorporation of heparan sulfate proteoglycan into complexes of fibronectin and collagen in the glomerular basement membrane and extracellular matrix (30). The anionic sites of heparan sulfate proteoglycan impart strong electronegativity to the glomerular basement membrane, and it is postulated that this charge effect helps keep the surface hydrated and prevents the filtration of negatively charged plasma protein such as albumin (31).…”
Section: Discussionmentioning
confidence: 99%
“…In poorly regulated diabetic patients, the degree of glycosylation of collagen IV and fibronectin is much higher than in control subjects (69). However, nonenzymatic glycosylation of collagen IV and fibronectin will decrease the affinity to HS-PG (69). This might lead to a greater turnover of HS-PG in poorly regulated diabetic patients (70) and reduced density of HS-PG in extracellular matrix.…”
Section: Causes Of Decreased Hs-pg In Diabetesmentioning
confidence: 96%
“…In poorly regulated diabetic patients, the degree of glycosylation of collagen IV and fibronectin is much higher than in control subjects (69). However, nonenzymatic glycosylation of collagen IV and fibronectin will decrease the affinity to HS-PG (69).…”
Section: Causes Of Decreased Hs-pg In Diabetesmentioning
confidence: 98%